Dynamics of Antibody Response to Yersinia pestis Proteins in Plague Affected Guinea Pigs - T. V. Gapel’chenkova; R. Z. Shaikhutdinova; A. S. Trunyakova; T. E. Svetoch; T. I. Kombarova; M. E. Platonov; A. I. Borzilov; P. Kh. Kopylov; S. V. Dentovskaya (Проблемы особо опасных инфекций, 2023)
Designing of new means for the specific prevention of plague, especially protein subunit vaccines, is impossible without studying the role of individual antigens in the manifestation of the pathogenic and immunogenic properties of Yersinia pestis. The aim of the present study was to determine the antibody levels to Y. pestis antigens in guinea pigs that survived infection with sub-lethal doses of virulent plague agent strains using enzyme immunoassay (ELISA). Materials and methods. Guinea pigs were inoculated subcutaneously with 30 CFU of the wild type Y. pestis subsp. Pestis strain 231 or non-capsular Y. pestis subsp. pestis Caf1-negative strain 358/12. Blood samples from sick or recovered guinea pigs were collected on day 15, 30, 60, and 90 after infection. The antibody response was assessed by 18 recombinant Y. pestis proteins in ELISA. Results and discussion. Heterogeneity of the antibody responses to the majority of the antigens with variation of IgG titers from animal to animal has been revealed. We observed increase in antibody titers by day 90 for the most analyzed antigens in the sera of the guinea pigs injected with wild type Y. pestis 231. On the contrary we found reduction in antibody titers by day 90 in case of inoculation with Y. pestis 358/12. The preservation of antibodies to Y. pestis proteins of different localization in the organism of the guinea pigs, as well functional activity, and the degree of representation on the surface of bacterial cell for a prolonged period of time indicates the multiplex nature of the plague immunity formation. Our ﬁndings are significant for the future design and development of effective vaccines against plague and the search for new targets for diagnostics of this disease.